Peran pendamping persalinan dalam mewujudkan pengalaman persalinan yang positif Diklinik Budi Mulia Palembang Tahun 2026 - Anggraini, Arli Febrianti , Tirta (STIKes Budi Mulia Sriwijaya, 2026)
A positive childbirth experience is an important indicator in midwifery services because it can improve maternal comfort, satisfaction, and psychological well-being after delivery. One of the factors influencing a positive childbirth experience is the presence of a birth companion who provides emotional, physical, and psychological support during labor. The support provided by birth companions can help mothers feel calmer, safer, and more confident in facing the childbirth process. This study aimed to determine the role of birth companions in creating a positive childbirth experience at Klinik Budi Mulia in 2026. This study used a quantitative method with an analytical design and a cross-sectional approach. The population consisted of all mothers giving birth at Budi Mulia Clinic Palembang in 2026. The sample included 40 respondents selected using an accidental sampling technique. Data were collected using questionnaires regarding the role of birth companions and positive childbirth experiences. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that most respondents received good birth companion support, namely 28 respondents (70%), while 12 respondents (30%) received less optimal support. Most respondents had a positive childbirth experience, namely 30 respondents (75%), while 10 respondents (25%) had a less positive childbirth experience. Statistical analysis showed a significant relationship between the role of birth companions and positive childbirth experiences with a p-value of 0.003 (p < 0.05). The conclusion of this study indicates that birth companions play an important role in creating a positive childbirth experience. Emotional support, motivation, attention, and assistance during labor can increase comfort, safety, and self-confidence among mothers during childbirth. Therefore, health workers, especially midwives, are expected to involve family members or husbands as birth companions to improve the quality of midwifery services and create positive childbirth experiences for mothers. Keywords: Birth Companion, Positive Childbirth Experience, Maternity Mothers, Midwifery.